Ariba implementation at MED-X : managing earned value - Jeffery, Mark, 1965- (SAGE Business Cases., 2006)
The Ariba Implementation at MED-X case is designed to teach students how to analyze a program that is experiencing problems and recommend solutions. Specifically, the case introduces students to earned value analysis and program oversight for an e-procurement technology program. The case centers on MED-X's need to quickly discover why the company's e-procurement implementation project was not going according to plan. Once a cause has been discovered students will need to make a recommendation to fix the problem. Data for the simplified program, consisting of two concurrent projects, is given to students in the case, who should in turn analyze the project using earned value analysis. The case is an easy introduction to program management and oversight for executives and MBA students, and teaches the essentials of earned value project management. This case and the associated teaching note are used as an introduction to project management in the Kellogg MBA course entitled Managing Technology Portfolios and Projects and in multiple Kellogg executive programs, including Driving Strategic Results through IT Portfolio Management.